BURNOUT SYNDROME IN THE MEDICAL PROFESSION: ORGANIZATIONAL AND INDIVIDUAL FACTORS : BURNOUT SYNDROME IN THE MEDICAL PROFESSION - Vukmirović, Marijana; Milic, Natasa (Medicinski podmladak, 2023)
The burnout syndrome represents a set of symptoms arising in a situation of prolonged stress at the workplace, in professionally demanding situations. It is characterized by emotional exhaustion, depersonalization and a sense of reduced personal accomplishment. In the 11th revision of the International Classification of Diseases, the World Health Organization defined burnout at work as an occupational phenomenon that affects health. The Maslach Burnout Inventory (MBI) is one of the tools used to measure the level of burnout. It has often been criticized for conceptual, methodological and practical reasons; however, it is still considered the gold standard for assessing job burnout and is used in 88% of all empirical studies. Factors that contribute to the development of burnout syndrome can be divided into organizational and individual factors. The complexity of work organization, as the crucial external factor, is reflected in the shaping of interpersonal relations, the establishment of hierarchies among employees, timely personnel planning and the need for professional training, which indirectly affects the degree of burnout of doctors at work. If one adds to that the need of doctors to engage in academic work, the failures in the medical system organization of the work are reflected in excessive working hours, devaluation of teaching work, inappropriate academic ranking, accumulation of engagements outside of teaching, pressure to publish papers and dissatisfaction with the criteria of scientific success. Personality traits, as the first and most important individual/internal factor, can speed up or slow down the occurrence of burnout syndrome at work due to the nature of their influence. They play a big role in making this syndrome noticeable in extroverted people and vice versa, causing it to remain unrecognized and hidden in introverted people. Thus, they make it difficult for this syndrome to be registered and delay the provision of timely assistance. The occurrence of burnout syndrome, which develops as a response to chronic professional stress, coupled with greater opportunities for professional development, better earnings and working conditions, as well as higher quality standards, are the key triggers of the migration of healthcare workers, both in Europe and in our country.